(untitled) (Research, Society and Development, 2021)
Introduction: Diabetes mellitus (DM) is a set of pathologies that have chronic hyperglycemia in common. The disease, and especially its poor control, can cause an increase in blood glucose and the high rates can lead to complications in the heart, arteries, eyes, kidneys and nerves, and, thus, the aim of this study is to demonstrate the main chronic complications resulting from diabetes mellitus. Objective: to highlight the main chronic complications resulting from diabetes mellitus. Methodology: This is a descriptive research of the narrative literature review type, which sought to answer what is the evidence on the long-term complications of diabetes mellitus. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases Information Services, October 2021. Results and discussion: Chronic diabetic complications are classified as microvascular or macrovascular, and contribute to mortality and loss of quality of life in patients with diabetes mellitus. From this perspective, it is noted that hyperglycemia plays a critical role in the pathogenesis of microvascular complications, such as diabetic retinopathy, incipient nephropathy and neuropathy, while atherosclerosis contributes to the pathogenesis of macrovascular complications. Conclusion: it is of paramount importance, when observing the relevance of lifestyle measures, the adoption of the practice of physical exercise in people with DM, especially in the elderly, that the glycemic control of patients with DM2 be effective, and thus controlling associated morbidities and chronicities.